Cord Blood Transplantations - Horwitz, Mitchell; Chao, Nelson; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
In this book, experts in the field express their well-reasoned opinions on a spectrum of important and complex issues in the area of cord blood transplantation. The aim is to provide practicing hematologists, including hematopoietic transplant physicians, with clinically relevant and immediately applicable information that will assist in the delivery of optimal care. The book opens by offering a historical perspective and examining current concepts and practices in cord blood banking. Sections are then devoted to strategies for cord blood graft selection and to areas of consensus and controversy in cord blood transplantation for neoplastic diseases - and nonmalignant - in children and adults. Attention is drawn to the implications of high-impact clinical trials whenever such trials are available. The readily intelligible text is complemented by numerous helpful tables, algorithms, and figures. This book will appeal to all residents, fellows, and faculty members responsible for the care of hematopoietic cell transplant patients and will offer a robust, engaging tool to aid vital activities in the daily work of every hematology and oncology trainee. .
Historical perspective and current trends -- Current cord blood banking concepts and practices -- Strategies for Cord Blood Graft Selection: Single or double cord blood unit for transplant: What have we learned?- Immunogenetics and cell dose considerations in cord blood transplants: What does matters?- Ex-vivo cord blood manipulation: Methods, data and challenges -- Conditioning regimens for cord blood transplants -- Cord blood transplants for non-neoplastic hematologic diseases: Data, consensus and challenges -- Cord Blood Transplants for Neoplastic Diseases in Children- Data, Consensus & Challenges: Cord blood transplants for myeloid malignancies in children -- Cord blood transplants for lymphoid malignancies in children -- Cord Blood Transplants for Neoplastic Diseases in Adults- Data, Consensus & Challenges: Cord blood transplants for myeloid malignancies in adults -- Cord blood transplants for lymphoid malignancies in adults -- Immune reconstitution after cord blood transplantation -- Cord blood transplants for non-hematopoietic disorders -- Cord blood transplants versus other sources of allografts: Comparison of data in adult setting -- Unique complications and limitations of cord blood transplants -- Future prospect of cord blood transplants. .
Keywords: Medicine; Hematology; Oncology; Medicine & Public Health; Hematology; Oncology